Fabrication and Application of Halloysite Nanotube-Embedded Photocatalytic Nanofibers with Antibacterial Properties - Gezmis-Yavuz, Elifnur; Ergon-Can, Tulay; Cansoy, C. Elif; Koseoglu-Imer, Derya Y. (American Chemical Society (ACS), 2022)
With decreasing indoor air quality, increased time spent at indoors, and especially with the COVID-19 pandemic, the development of new materials for bacteria and viruses has become even more important. Less material consumption due to the electrospinning process, the easy availability/affordability of the halloysite nanotube (HNT), and the antibacterial effect of both TiO2 and ZnO nanoparticles make the study even more interesting. HNTs have attracted research attention in recent years due to their low cost, high mechanical strength, natural and environmentally friendly structure, and non-toxicity to human health and ecosystem. In this study, HNT-embedded composite nanofiber filters were fabricated as filter materials using the electrospinning method. Photocatalysts (TiO2 and ZnO) were incorporated into the composite nanofibers by the electrospraying method. The results showed that the combination of both HNT/TiO2 and HNT/ZnO additives was successfully integrated into the filter structure. The effect of embedding the HNT and spraying photocatalysts enables the fabrication of composite filters with lower pressure drop, high filtration efficiency, improved mechanical properties, and high antibacterial properties against Escherichia coli, making the nanofibers suitable and promising for face masks and air filter materials.
Keywords: Chemistry; QD1-999